The efficacy and safety of Hanslim for obese patients: Study protocol for a multicenter, randomized, double-blind, multi-dose, placebo-controlled, phase IIb clinical trial. Issue 38 (September 2018) - Lee, Seunghoon; Lee, Hyeonhoon; Cho, Yeeun; Kim, Jihye; Kang, Jung Won; Seo, Byung-Kwan; Baek, Yong-Hyeon; Lee, Jae-Dong
Abstract: Background: This study aims to evaluate the efficacy, safety, and appropriate dose of Hanslim, a Korean traditional herbal medicine, for obese patients, when compared to a placebo. Methods/design: This study is a randomized, double-blinded, multicenter, multidose, placebo-controlled, phase IIb clinical trial. A total of 165 obese patients with a body mass index (BMI) of more than 30 kg/m 2 or obese patients with a BMI of 27 to 29.9 kg/m 2 and one or more risk factors such as hypertension, diabetes, or hyperlipidemia will be enrolled. Participants will be randomly assigned to 1 of 3 groups (high-dose, low-dose, or placebo) with a 1:1:1 allocation ratio and will have 4 scheduled visits during the 12-week treatment period. The participants will be administered 2 tablets of Hanslim or placebo, 2 times per day. The difference in the proportion of participants who lost weight by more than 5% from their baseline at 12 weeks compared to the placebo group will be examined as the primary efficacy outcome. Secondary efficacy outcomes include differences in body weight, BMI, body-fat percentage, fat mass, skeletal-muscle mass, edema index, waist circumference, hip circumference, waist-hip ratio, serum lipid, blood glucose, C-reactive protein, and total score of Korean version of obesity-related quality of life after 12 weeks of treatment. Adverse events, laboratory test results, vital sings, and electrocardiography will be recorded to evaluate safety. Discussion: This is the first prospective clinical trial to explore the efficacy and safety of Hanslim for obese patients. If the results provide the appropriate dosage of Hanslim, this study would contribute to the confirmatory evidence for the use of Hanslim as a treatment for obesity needed to conduct a large-scale, phase III clinical trial. The results will be published in a peer-reviewed journal. Trial registration: Clinical Research Information Service, ID: KCT0002193. Registered on January 6, 2017.https://cris.nih.go.kr/cris/search/search_result_st01_en.jsp?seq=7468